2016
DOI: 10.1097/iae.0000000000000999
|View full text |Cite
|
Sign up to set email alerts
|

Epiretinal Membrane–induced Full-Thickness Macular Holes

Abstract: Epiretinal membrane-induced FTMH has distinct features from the typical Stage 2 or 4 FTMH. Despite the small size, visual improvement is not as good as that in Stage 2 FTMH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 14 publications
4
41
1
Order By: Relevance
“…It has been already reported that the preoperative smaller FTMH diameter was a prognostic factor of better postoperative functional and structural outcomes [ 12 ]. The notable result in our study was the inverse relationships of the presence of LHEP with postoperative functional and morphological outcomes, which is consistent with the previous study [ 10 ]. These results strongly support the hypothesis that FTMH with LHEP develops first with processes of photoreceptor damage following LMH formation and later outer laminar dehiscence.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It has been already reported that the preoperative smaller FTMH diameter was a prognostic factor of better postoperative functional and structural outcomes [ 12 ]. The notable result in our study was the inverse relationships of the presence of LHEP with postoperative functional and morphological outcomes, which is consistent with the previous study [ 10 ]. These results strongly support the hypothesis that FTMH with LHEP develops first with processes of photoreceptor damage following LMH formation and later outer laminar dehiscence.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, there was no difference in the smallest FTMH diameter between FTMH with and without LHEP. This result is at odd with previous reports [ 10 , 11 ]. This discrepancy in results may be due to the existence of two different shapes in FTMH with LHEP.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…A less common mechanism of MH formation is by ERM traction, usually on a lamellar macular hole (LMH) [ 52 ]. Recently, a study proposed by Pang and associates [ 53 ] found that the lamellar hole-associated epiretinal proliferation (LHEP) appears on SD-OCT images as a substantial material of homogenous medium reflectivity located on the epiretinal surface, which is a unique feature in LMH or LMH-induced full-thickness macular hole (FTMH).…”
Section: The Surgical Outcomesmentioning
confidence: 99%